HABITUAL PHYSICAL ACTIVITY AMONG PHYSICAL EDUCATION COLLEGE STUDENTS (Fiep Bulletin - online, 2014)
The purpose of this study was to provide descriptive data about habitual physical activity levels in representative sample of physical education college students of the Faculdade Estadual de Educaçao Fisica de Jacarezinho - PR (FAEFIJA). A sample of 100 of the 395 enrolled students were included in the study. The short version of the International Physical Activity Questionnaire (IPAQ) was used to assess the habitual physical activity. The results showed that the average of age of the students was  23,5 years, 75% work in a paid way, 95% of the students don't smoke and 51% don't consume alcohol which indicates healthy. The average medium index body mass found was of 22.34 kg/m2, and 78% are with normal weight. About the level of habitual physical activity accomplished by the students, there are indications that most already practiced exercises before entering in FAEFIJA and they didn't lose the habit, which indicates that such behaviors might have influenced when they made the option for the course of physical education. Of those researched, 67% are among the physically active and many active, what takes to have faith that there is a concern as for the lifestyle.
Keywords: Physical Activities; Health; Behavior; IPAQ